(Ne)prisotnost starizma v zdravstvenem okolju - Hreščak, Larisa (Kakovostna starost, 2025)
Ageism is a form of discrimination that can be subtle or institutionalised, particularly in healthcare settings where discriminatory practices are o2en normalised. Such negative attitudes towards older adults can signi- )cantly a'ect the quality of healthcare and reduce their social and health opportunities. *e study was based on a quantitative methodology using an online survey. *e sample consisted of 204 healthcare professionals with di'erent pro)les aged between 21 and 65 years. *e survey included demographic questions, questions about personal experiences with older adults and the Slovenian translation of the Fraboni Scale of Ageism, which is designed to measure prejudice against older people. A higher score indicates a stronger presence of ageism, while a lower score re,ects a more positive attitude. Statistical analysis included one-sample t-tests, independent samples t-tests, one-way analysis of variance (ANOVA), and Pearson’s correlation coe+cient. *e mean score on the Fraboni Scale of Ageism (M = 56.26, SD = 6.61) was signi)cantly below the theoretical cut-o' point of 70 (p 0.05). *e results suggest that healthcare professionals do not express pronounced ageism tendencies, however, di'erences are evident depending on gender and individual circumstances. To reduce potential biases, it would be advisable to include more content on ageing and intergenerational solidarity into healthcare education and to strengthen the positive image of ageing within society.
Keywords: age discrimination; ageism; healthcare; inequality; neenakost; starizem; starostna diskriminacija; zdravstvena oskrba